2006
DOI: 10.1063/1.2180878
|View full text |Cite
|
Sign up to set email alerts
|

Improved ferroelectric property of LaNiO3∕Pb(Zr0.2Ti0.8)O3∕LaNiO3 capacitors prepared by chemical solution deposition on platinized silicon

Abstract: We report a technique to prepare top and bottom oxide electrodes of LaNiO3 (LNO) for lead zirconate titanate (PZT) films using a chemical solution deposition. LNO/PZT/LNO sandwich structures were prepared on platinized silicon by spin coating combined with rapid thermal annealing. Pt dots were sputtered on top of LaNiO3 film to serve as protective masks during etching of the uncovered LaNiO3 layer using dilute hydrochloric acid. For comparison, Pt/PZT/Pt capacitors were also prepared using the same processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…In the past, extensive efforts have been made on preparing ferroelectric thin films on Pt metallic electrodes, but the ferroelectric films have been easily fatigue degraded and further more it was difficult to grow highly (1 0 0)-oriented BTO films directly on Pt-coated silicon (Si) substrate. Recent researches on ferroelectric films preparation revealed that some perovskite-related metallic oxides, such as YB 2 Cu 3 O 7Àx (YBCO), La 0.5 Sr 0.5 CoO 3 (LSCO), SrRuO 3 (SRO) and LaNiO 3 (LNO), could be employed as electrodes not only for the great improvement of fatigue and aging of ferroelectric films but also help to form certain orientations [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, extensive efforts have been made on preparing ferroelectric thin films on Pt metallic electrodes, but the ferroelectric films have been easily fatigue degraded and further more it was difficult to grow highly (1 0 0)-oriented BTO films directly on Pt-coated silicon (Si) substrate. Recent researches on ferroelectric films preparation revealed that some perovskite-related metallic oxides, such as YB 2 Cu 3 O 7Àx (YBCO), La 0.5 Sr 0.5 CoO 3 (LSCO), SrRuO 3 (SRO) and LaNiO 3 (LNO), could be employed as electrodes not only for the great improvement of fatigue and aging of ferroelectric films but also help to form certain orientations [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tel. : +86 312 5977033; fax: +86 312 5011174. one of the most promising materials for ferroelectric electrodes [13]. Although many results related to LNO electrodes of PZT capacitors have been published [14,15], impact of LNO bottom electrodes grown at various temperatures on the structural and physical properties of PZT capacitors is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that PZT deposited on Pt electrodes started to lose remanent polarization dramatically after 10 6 cycles. 6 More recent research work found that the fatigue problem could be improved up to 10 11 cycles by using conductive oxides electrodes such as RuO 2 , SrRuO 3 , IrO 2 , La 1Àx Sr x CoO 3 (LSCO), YBa 2 Cu 3 O 7Àx , and LaNiO 3 . 7-11 Among those conductive oxides, LaNiO 3 is widely used as a bottom electrode material for ferroelectric thin-film capacitors because of its good electrical conductivity and low processing temperature.…”
Section: Introductionmentioning
confidence: 99%